Given that:
f(x) = -2x²-2x+10
f(2) = -2(2)²-2(2)+10
= -2(2*2) - 4 + 10
= -2(4) - 4 + 10
= -8 - 4 + 10
= -12 + 10
= -2 Ans.
Read more:
Similar Question
Given f(x) = 1/2x - 5, find f^-1(x) a. f^-1 (x) = -2x+10 b. f^-1(x) = 2x+5 c. f^-1(x) = 2x-10 d. f^-1(x) = 2x+10...
brainly.com/question/11148895?referrer
Answer:
Step-by-step explanation:
Hello!
Good luck!
Answer:
<h2><em><u>hope </u></em><em><u>it </u></em><em><u>helps </u></em><em><u>you </u></em><em><u>see </u></em><em><u>the </u></em><em><u>attachment </u></em><em><u>for </u></em><em><u>further </u></em><em><u>information </u></em><em><u>(๏_๏)</u></em><em><u>(๏_๏)</u></em><em><u>(๏_๏)</u></em></h2>
Distribute multiplication over addition and subtraction:
3x+ 12y+10x-5y
Combine like terms:
13 x +7y